Peningkatan Hasil Belajar Bahasa Indonesia Materi Menulis Karangan Narasi Menggunakan Model Pembelajaran Concept Sentence di SDN Sidorejo 2 Kabupaten Barito Kuala - Nurul Huda Fitriani; Nadya Huda; M. Ihsan Ramadhani (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the quality of teacher activity, student activity and to improve student learning outcomes in learning Indonesian in narrative essay writing material. This study uses a qualitative research approach with the type of Classroom Action Research (CAR). The setting of this research was carried out at SDN Sidorejo 2 Barito Kuala Regency in the even semester of the 2021/2022 academic year with a total of 26 students. Data collection techniques in this study were qualitative data and quantitative data, which were obtained through observing teacher activities, observing student activities, and learning outcomes through evaluation tests. Data analysis with descriptive analysis techniques presented in the table is interpreted with the percentages and indicators of learning completeness determined. The results showed that the quality of the teacher's activities from cycle I was carried out with good criteria, cycle II was carried out with very good criteria. Student activities in cycle I reached the criteria of good, and cycle II achieved very good criteria. The classical completeness of student learning outcomes from cycle I and cycle II increased from 73% to 84%. Based on these findings it can be concluded that the Concept Sentence learning model can increase student learning activities so that the hypothesis can be accepted. It is suggested that the Concept Sentence learning model can be used as an alternative in increasing student activity which has an impact on improving student learning outcomes.